2010
DOI: 10.1016/j.joca.2009.10.005
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of five approaches to measurement of anatomic knee alignment from radiographs

Abstract: Objective The recent recognition of the correlation of the hip-knee-ankle angle (HKA) with femur-tibia angle (FTA) on a standard knee radiograph has led to the increasing inclusion of FTA assessments in OA studies due to its clinical relevance, cost effectiveness and minimal radiation exposure. Our goal was to investigate the performance metrics of currently used methods of FTA measurement to determine whether a specific protocol could be recommended based on these results. Methods Inter- and intra-rater rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 20 publications
(16 reference statements)
2
55
0
Order By: Relevance
“…Concurrent validity between measurement methods was modest and consistent with previous studies [5][6][7][8][9][10][11]15,26], and correlations were similar when stratifying for sex and JSN. IranpourBoroujeni et al [12] reported correlations with HKA using the traditional FTA method (r ¼ 0.68) and the new FTA method (r ¼ 0.75), which were larger than those reported in the present study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Concurrent validity between measurement methods was modest and consistent with previous studies [5][6][7][8][9][10][11]15,26], and correlations were similar when stratifying for sex and JSN. IranpourBoroujeni et al [12] reported correlations with HKA using the traditional FTA method (r ¼ 0.68) and the new FTA method (r ¼ 0.75), which were larger than those reported in the present study.…”
Section: Discussionsupporting
confidence: 86%
“…Underestimating the magnitude of alignment at both ends of the continuum further highlights the limited utility of this measurement tool, rendering goniometry inadequate for use in a clinical environment. Of the few studies that have evaluated the relationship between goniometry and radiographic alignment, poor consensus has been established [5,6,26]. This inconsistent evidence is most likely an outcome of the relatively large random error and potentially low precision of the goniometer measurement, as well as measurement variability between different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation for the difference may also be due to observation errors when evaluating WLR's. This however does not appear to be a problem since HKA angle measurements on standing WLR are relatively reliable with a standard error of less than 1.5° [21].…”
Section: Discussionmentioning
confidence: 99%
“…The baseline KL scores did not differ significantly between the progressors and non-progressors (p=0.36). Because alignment may influence the risk of progression, we measured baseline alignment using the femur-tibia angle measure (method B) reported by McDaniel et al 24 . There was a difference in the mean baseline alignment angle but it was not significant due to the large variability (progressors 0.96±5.06, mean±SD, non-progressors −1.46±3.78; p=0.08).…”
Section: Methodsmentioning
confidence: 99%